2009
DOI: 10.1126/science.1177321
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose)–Dependent Regulation of DNA Repair by the Chromatin Remodeling Enzyme ALC1

Abstract: SummaryALC1, a novel PARP1-stimulated chromatin-remodelling enzyme promotes DNA repair.Post-translational modifications play key roles in orchestrating chromatin plasticity. Although various chromatin-remodelling enzymes have been described that respond to specific histone modifications, little is known about the role of poly(ADP-ribose) in chromatin remodelling. Here, we identify a novel chromatin-remodelling enzyme, ALC1 (Amplified in Liver Cancer 1), that is specifically regulated by poly(ADP-ribosyl) ation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
614
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 533 publications
(652 citation statements)
references
References 32 publications
26
614
0
5
Order By: Relevance
“…3D). Comparing the results of the two CHD1L mutants, the mutation of the CHD1L macro‐domain led to a more prominent reduction in the PARP1/CHD1L interaction, indicating that the macro‐domain of CHD1L is the major PAR binding motif, as described by previous biochemical studies 22, 23. Collectively, these data indicate that PAR affinity for CHD1L is crucial for the interaction between PARP1 and CHD1L, especially at the functional macro‐domain, during early reprogramming.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…3D). Comparing the results of the two CHD1L mutants, the mutation of the CHD1L macro‐domain led to a more prominent reduction in the PARP1/CHD1L interaction, indicating that the macro‐domain of CHD1L is the major PAR binding motif, as described by previous biochemical studies 22, 23. Collectively, these data indicate that PAR affinity for CHD1L is crucial for the interaction between PARP1 and CHD1L, especially at the functional macro‐domain, during early reprogramming.…”
Section: Resultssupporting
confidence: 76%
“…3A, right). It has been shown that the macro‐domain of CHD1L serves an essential role for PAR binding and PARP1‐dependent recruitment of CHD1L to DNA damage sites 22, 23. To determine whether the macro‐domain of CHD1L is involved in the PARP1/CHD1L interaction during cell reprogramming, CHD1L wild‐type (CHD1L‐WT) and two mutant types—a helicase‐domain mutant (CHD1L‐K77R) and macro‐domain mutant (hCHD1L‐D723A)—were ectopically expressed in MEFs with OSKM transfection for 6 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCNA is a ring-shaped clamp around DNA that serves as a loading platform for proteins involved in DNA replication and repair [14]. ALC1 is an SNF2-type chromatin remodeling ATPase, which is activated upon PAR binding to its macro domain at DNA damage sites [15,16]. PARP1, PARG, PCNA and ALC1 are all recruited to laser-induced DNA damage sites albeit with distinct recruitment kinetics.…”
Section: Introductionmentioning
confidence: 99%